Choroidal thickness changes in post-COVID-19 cases - Konuk,Şerife Gülhan (2022)
ABSTRACT Purpose: The current study aimed to evaluate the effects of the coronavirus disease 2019 (COVID-19) on choroidal thickness using enhanced depth imaging optical coherence tomography. Methods: This study evaluated the right eyes from 41 post-COVID-19 cases (Group 1) and 41 healthy subjects (Group 2). Choroidal thickness was measured using enhanced depth imaging optical coherence tomography. Post-COVID-19 cases were evaluated within 1 month after a diagnosis of COVID-19. Two experienced ophthalmologists measured the choroidal thickness at the subfovea, temporal, and nasal quadrants at 500-μm intervals up to 1500 μm from the fovea at seven different points. Moreover, central macular thickness and ganglion cell layer thickness were measured via OCT, after which both two groups were compared. Results: Group 1 showed a significantly thicker choroid compared to Group 2 at the subfovea, 500 μm temporal to the fovea, 500 and 1000 μm nasal to the fovea (p=0.011, p=0.043, p=0.009, and p=0.019, respectively). Although other areas measured were also thicker in Group 1, the difference was not significant (p>0.05). Moreover, no significant difference in the central macular thickness and ganglion cell layer thickness were observed between the groups (p>0.05). Conclusion: Choroidal thickness was increased in post-COVID-19 patients, which might be related to inflammation associated with the pathogenesis of COVID-19.